Various Bouquets Creative Industry Training on Village Women Business Group to Improve Family Income at Timbang Deli Village, Deli Serdang Regency - Deliana; Kumalasari, Fauziah; Nurlela (Talenta Publisher, 2023)
Timbang Deli Village is one of the villages at Deli Serdang Regency that has village’s women business group (UP2K-PKK) to improve family income. In this village, there has not been much training or counseling about creative industries. One form of the creative industry is bouquet making. A bouquet is a series or decoration with various forms of variations given at certain moments. This training aims to 1) increase the income of village women's business groups through the creative industry for making bouquets, 2) utilize social media as a means for marketing bouquet products. The approach method used is to collaborate with partners, the government, and the PKK group by conducting counseling and training and mentoring methods to start a bouquet business. This training was considered successful to increase partner’s knowledge and skills in bouquet arrangement.